Pengaruh Faktor Peraturan Wali Kota, Tarif Sewa, dan Aksesibilitas terhadap Keputusan Pedagang dalam Memilih Lokasi Usaha di Luar Area Resmi Pasar Pasir Gintung Kota Bandar Lampung dalam Perspektif Etika Bisnis Islam: Studi pada Pedagang Pasar Pasir Gintung Kota Bandar Lampung - Sabrina Aulia; Liya Ermawati; Oza Restianita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The presence of traders operating outside the official area of Pasir Gintung Market in Bandar Lampung indicates that the implementation of market arrangement policies by the local government has not been fully effective. This condition is presumed to be influenced by mayoral regulations, rental rates, and accessibility as key considerations for traders in determining business locations. This study aims to analyze the effect of mayoral regulations, rental rates, and accessibility on traders’ decisions to choose business locations outside the official market area from the perspective of Islamic Business Ethics. This study employs a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 78 traders operating outside the official market area using purposive sampling. Data were analyzed using multiple linear regression, including t-test, F-test, and coefficient of determination. The results indicate that partially, mayoral regulations and rental rates do not have a significant effect on traders’ decisions, while accessibility has a significant effect. Simultaneously, the three variables influence traders’ decisions. From the perspective of Islamic Business Ethics, traders’ decisions have not fully reflected compliance with regulations aimed at achieving public welfare.